AN ANALYSIS OF PARENT’S LOVE EXPRESSION UTTERANCES AS THE IDENTITY OF CHILDREN PARENTING AT THE ISLAMIC SCHOOL: A DISCOURSE ANALYSIS POINT OF VIEW (ANALISIS UNGKAPAN EKSPRESI CINTA ORANG TUA SEBAGAI IDENTITAS ANAK PENGASUHAN ANAK DI SEKOLAH ISLAM: SUDUT PANDANG ANALISIS WACANA) - Jarudin Jarudin; Amir Husin Mohd Nor Mohd Nor; Edwar Kemal; Wahyudi Rahmat; Fahmi Zahiddan Rauf (Universitas PGRI Sumatera Barat, 2022)
The presence of children in household life challenges the parents, particularly in terms of how to grow and educate them. The first step in establishing communication between children is towards the use of language and expressions. The language used varies and will continue to change as the child's life and age progress. This paper aims to elaborate on the instructions of the Qur'an and Sunnah regarding the language style that parents should use when educating their children. This research used qualitative research used library research towards secondary data in the form of interpretations of Quranic verses and Sunnah explanations of parental language styles and expressions in educating children found in Islamic teachings. The data were analyzed using a content analysis approach and added by theory of discourse analysis. The research shows that the Qur'an and Sunnah have guided parents to use polite, gentle, and loving language in educating their children regardless of their age or the good or bad of their behavior. The language discourses used by the parents to teach the children have already been stated into alquran and sunnah based on the ages of the children itself.